Dynamic Linkages between Remittances, Domestic Expenditure, Exports, and Economic Growth in ASEAN Economies - Abduh Afif; Tajul Ula; Chahayu Astina (Journal of Enterprise and Development (JED), 2026)
Purpose: This study examines the dynamic relationship between remittances, gross national expenditure, exports, and economic growth in selected ASEAN countries. It specifically investigates how these variables interact in the short and long run and their contribution to regional economic performance.Method: A quantitative explanatory approach was employed using panel data from five ASEAN countries over the period 1999–2024, comprising 130 observations. Data were obtained from the World Development Indicators (WDI) database published by the World Bank. The analysis applied the Pooled Mean Group–Autoregressive Distributed Lag (PMG–ARDL) model to estimate both short-run and long-run relationships while accounting for cross-country heterogeneity.Result: The findings reveal that remittances, gross national expenditure, and exports significantly promote economic growth in the long run. Remittances contribute by increasing household income and supporting consumption, while gross national expenditure strengthens domestic demand. Exports enhance growth through external market expansion and improved trade performance. However, the short-run effects are relatively limited, suggesting the presence of structural constraints and varying adjustment capacities across ASEAN economies.Practical Implications for Economic Growth and Development: The results highlight the need for balanced growth strategies that integrate remittance management, domestic demand expansion, and export diversification. Strengthening institutional quality, financial inclusion, and fiscal discipline is essential to maximize the developmental impact of these growth drivers.Originality/Value: This study offers updated empirical evidence on the determinants of long-run economic growth in ASEAN using a PMG–ARDL framework, providing insights into both regional integration and country-specific economic dynamics.